2018
DOI: 10.1177/1059840518813697
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Worklife and Levels of Burnout Surveys to Assess the School Nurse Work Environment

Abstract: Previous research regarding burnout in acute care settings revealed that positive work environments increase job satisfaction, decrease staff turnover, and improve patient outcomes. However, few studies address burnout among school nurses. The purpose of this study was to describe the relationship between the school nurse practice environment, school nurses’ levels of burnout, and perceived sources of work stress. A cross-sectional sample of 100 registered nurses completed a web-based version of the Maslach Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
2
26
0
1
Order By: Relevance
“…In case of the relationship of perceptions of the work environment→job burnout model, the results in this study are in accord with two China's studies (Qian et al, 2020;Wu et al, 2020) and a study in the western country (Jameson & Bowen, 2018). Similarly, multiple studies indicate abusive supervision (Wu & Hu, 2009), organizational injustice (Manville et al, 2016), quality of the employee-manager relationship (Medler-Liraz & Seger-Guttmann, 2017), changing job characteristics (Bernhard-Oettel et al, 2018), and employees' work reflection (Walter & Haun, 2020) initiates emotional exhaustion.…”
Section: Discussionsupporting
confidence: 81%
“…In case of the relationship of perceptions of the work environment→job burnout model, the results in this study are in accord with two China's studies (Qian et al, 2020;Wu et al, 2020) and a study in the western country (Jameson & Bowen, 2018). Similarly, multiple studies indicate abusive supervision (Wu & Hu, 2009), organizational injustice (Manville et al, 2016), quality of the employee-manager relationship (Medler-Liraz & Seger-Guttmann, 2017), changing job characteristics (Bernhard-Oettel et al, 2018), and employees' work reflection (Walter & Haun, 2020) initiates emotional exhaustion.…”
Section: Discussionsupporting
confidence: 81%
“…For school nurses, autonomy involves having control and opportunities to independently adjust and creatively make decisions for their nursing practice (Broussard, 2007; Foley et al, 2004; Simmons, 2002). The opportunity to make such independent choices affects nurses’ job satisfaction (Crilly et al, 2019; Curtis & Glacken, 2014; DeSisto & DeSisto, 2004; Graham et al, 2011; Halter et al, 2017; Lin et al, 2007; Seren Intepeler et al, 2019) and influences their remaining in practice (Andresen et al, 2017; Jameson & Bowen, 2018). However, as this study and previous research (Skundberg‐Kletthagen & Moen, 2017; Thunman, 2012) indicate high workload or limited scope to influence work tasks prevents nurses from practising nursing the way they want to.…”
Section: Discussionmentioning
confidence: 99%
“…The professional competence of school nurses varies across international settings, but their work tasks are congruent and often regulated by the government (Baltag et al, 2015; Glavin et al, 2013; Willgerodt et al, 2018). A number of national and international studies have reported that school nurses experience complex nursing situations and heavy workload (Clancy, 2010; Curtis & Glacken, 2014; Foley et al, 2004; Jameson & Bowen, 2018; Markham & Carney, 2008; Skundberg‐Kletthagen & Moen, 2017), and school nurses leave work if they feel they do not have the skills or working conditions to manage their work tasks (Sendall et al, 2014). For instance, it is documented that experiencing limited influence on work tasks represents a risk for burnout (Thunman, 2012), and heavy workload can contribute to a lower level of autonomy due to lack of time and complicated tasks (Graham et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The scale examines the dimensions of an individual’s work life and predicts their relationship with burnout 31 . It has been widely used 32 33 and validated (Cronbach’s alpha: 0.71 to 0.85) 31 in healthcare settings. The six dimensions assessed in the survey were: workload, control, reward, community, fairness, and values.…”
Section: Methodsmentioning
confidence: 99%